2018
DOI: 10.18488/journal.1.2018.811.968.973
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Development of the Laws Relating to Child Sexual Exploitation Prior to the Passing of the UNCRC in 1989

Abstract: The abuse of children for sexual purposes has a long-standing history. It evolved due to many factors such as disparity in gender, misled religious beliefs, acceptable customary practices, superstition and economic development and it remains severe globally. The United Nations Children's Fund ("UNICEF") estimated in 2014 that about 120 million girls under the age of 18 have been subjected to forced sexual acts at some point of their lives. Even though this statistic covers all categories of sexual abuse, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results of the survey indicated that only 39 percent have a formal risk management program and that over 40 percent of the agencies felt that their risk management procedures were not effective. The results also indicated that executives play a critical role in a risk management program; employees must be involved at all stages in the development of the risk management program; adequate resources should be allocated for implementing risk management; and, in developing a risk-aware culture, it should involve everyone in the organisation (Rosli & Dusuki 2018). The leading human behavioural factors for risk-aware culture highlighted in this study are the critical role of executives, rearticulated as top management support; and, employee's involvement.…”
Section: Determinants For Risk-aware Culturementioning
confidence: 99%
“…The results of the survey indicated that only 39 percent have a formal risk management program and that over 40 percent of the agencies felt that their risk management procedures were not effective. The results also indicated that executives play a critical role in a risk management program; employees must be involved at all stages in the development of the risk management program; adequate resources should be allocated for implementing risk management; and, in developing a risk-aware culture, it should involve everyone in the organisation (Rosli & Dusuki 2018). The leading human behavioural factors for risk-aware culture highlighted in this study are the critical role of executives, rearticulated as top management support; and, employee's involvement.…”
Section: Determinants For Risk-aware Culturementioning
confidence: 99%